A Study on Base Processes for Selected Reactions of Microreactors: Advantages and Applications of Microreactors in Chemical Reactions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
For a variety of chemical reactions Microreactors have outstanding mass and heat transfer efficiency. In terms of energy performance, yield, protection, reliability and scalability, the usage of micro-reactors provides also advantages over traditional reactors. In comparison to the batch phase, Microreactors dissipate heat efficiently and also very exothermal. Also if micro reactors will synthesize chemical products in limited amounts only, the amount of micro channels can be added to the industrial phase. The study discussing micro-reactors characteristics, Experimental process for nickel nanoparticles synthesis in Microreactors, Heterogeneous catalytic response Microreactors, Microreactors building, Microreactors' advantages Comparison of batch and micro-reactors Comparison various forms of reactorsdevices used in chemical industries for process intensification